Sistem Komunikasi Mikrokontroler dan PLC Berbasis Komunikasi Serial Host Link dan Protokol C-Command RS232 - Ruwahida, Dewi Rizani Ruwahida; Rachman, Isa; Widodo, Hendro Agus; Adhitya, Ryan Yudha; Irawan, Yuda (Infotekmesin, 2023)
The communication between microcontrollers and PLC has become an important technology development that needs to be enhanced. One of the reasons for the communication between these two devices is to facilitate the input process of data or information from sensors, which are responsible for detecting or measuring specific parameters. Not all sensors can be directly read by PLC, as some sensors have their own communication protocols or specific libraries that are not directly supported by PLC. Microcontrollers are often used as intermediaries between sensors and PLC. Microcontrollers can read sensor data and then convert it into a format that can be understood by PLC. Microcontrollers can perform flat processing tasks such as conversion and status evaluation to provide more relevant data, and then send this data to the PLC through a compatible communication protocol. In this study, the communication protocol used is the Host Link serial communication using the C-mode Command method. The communication testing conducted using 10 different data samples resulted in accurate values with an error percentage of 0%.